HUBUNGAN ANTARA HARGA DIRI DENGAN KEBERMAKNAAN HIDUP PADA USIA LANJUT USIA DI PANTI SOSIAL X SLEMAN YOGYAKARTA - Eni Rohyati; Dewi Fitri Yani (LPPM Universitas Proklamasi 45, 2024)
ABSTRACT This study discussed the relationship between self-esteem and meaningfulness of life in elderly residents living in nursing home X in Sleman Yogyakarta. The number of residents of the nursing home is 113 elderly, of which 100 elderly are regular program participants and the remaining 13 are cross-subsidy program participants. The research sample was 50 elderly (25 women and 25 men), with characteristics of age 60-70 years, healthy physical condition, and able to communicate. The hypothesis of this study is proven, namely the higher the self-confidence of an elderly person, the higher the meaningfulness of his life with rxy = 0.434 with (p) = 0.002 (p <0.01). Keywords: Elderly, Self-Esteem, Meaningfulness of Life.